Squat to Work. Squatted Workspaces, the Commons and Solidarity Economies in Europe - Calafati, Luca (PARTECIPAZIONE E CONFLITTO, 2020)
Inspired by recuperated enterprises in Latin America, squatted workspaces have emerged across Southern Europe in the aftermath of the 2008 crisis. Using the literature on European squatting, the concept of the commons and an action research in a squatted workspace in Milan, Italy, the paper explores the re-emergence of this type of squatting and its relation to solidarity economies in contemporary Europe. The paper examines how precarious workers have used squatting to establish self-managed workspaces to access income and to reinvent work and economic relations beyond capitalism. The paper also investigates the ambivalent role of squatting in supporting the establishment of solidarity economies.